2005
DOI: 10.1080/02770900500264770
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Probable Mental Disorders Among Pediatric Asthma Patients in an Inner-City Clinic

Abstract: These findings are the first to provide preliminary evidence suggesting that mental health problems are common among pediatric asthma patients in an inner-city clinic. The results also suggest that mental health problems in pediatric asthma patients may be associated with elevated levels of medical service use for asthma. Replication of this pilot study is needed with a larger sample, more precise diagnostic methodology, and a comparison group with chronic medical illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
55
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 36 publications
10
55
1
1
Order By: Relevance
“…Contrary to our conclusions, several prior cross-sectional studies showed that probable PD, including anxiety or depression symptoms, was not significantly associated with higher levels of medical services for asthma (10,30,31). However, the cross-sectional study design and possible recall bias may weaken the validity of these cross-sectional studies.…”
Section: Discussioncontrasting
confidence: 55%
“…Contrary to our conclusions, several prior cross-sectional studies showed that probable PD, including anxiety or depression symptoms, was not significantly associated with higher levels of medical services for asthma (10,30,31). However, the cross-sectional study design and possible recall bias may weaken the validity of these cross-sectional studies.…”
Section: Discussioncontrasting
confidence: 55%
“…The WHO estimates that there are currently 300 million people suffering from asthma and asthma is also estimated to account for ,250,000 deaths per year worldwide [12,13]. Asthma can have a significant effect on quality of life, and consequences include sleeplessness, daytime fatigue, reduced activity levels, school and work absenteeism, and mental health problems [14][15][16]. It is hypothesised that asthma is a risk factor associated with suicidal behaviour.…”
mentioning
confidence: 99%
“…Asthma and PD are both characterized by acute episodes, salient respiratory symptoms and anxiety with avoidance of situations related to acute attacks (Klein, 1993;Yellowlees and Kalucy, 1990). There is a significantly higher (6.5 to 24%) prevalence of PD in asthmatics (Goodwin et al, 2005;Shavitt et al, 1992;Yellowlees et al, 1988) than the 1-3% reported in the general population (Kessler et al, 2006;Weissman, 1988). Perna et al (1997) found a significantly higher prevalence of PD, sporadic panic attacks, and social phobia in asthmatics than the general population.…”
Section: Panic and Comorbid Conditionsmentioning
confidence: 69%